GENETIC DIVERSITY AND MOLECULAR TAXONOMY STUDY OF GENUS FESTUCA - A. Alsaleh1; M. C. Dogrusoz; U. Basaran; A. Tamkoc; M. A. Avci (Journal of Animal and Plant Sciences, 2020)
The genus Festuca (Poaceae) occupies a wide range of lands in both hemispheres, with astounding significance endowed by the genetic diversity, intra/inter-species discriminations, and structure analysis of Fescue species based on a reliable molecular marker. While still in the infancy stage, information on genetic structure and relationships of Festuca species from Turkish gene pool have rarely, or never, been subjected to the most needed studies. Six species of genus Festuca were put in the limelight. A total of 598 loci were generated through molecular characterization of 68 accessions by using 19 inter-simple sequence repeats primers. Molecular variance revealed a variation within species and among species of 75% and 25, respectively. The F. ovina showed high values in relation to the number of different alleles, Shannon's information index, and percentage of polymorphic loci. The highest genetic variability, expected and unbiased expected heterozygosity values were detected for F. arundinacea. Nei genetic distance showed that the lowest value was found between F. ovina and F. valesiaca species, while the highest was identified between F. heterophylla and F. pratensis species. An obvious convergence has been detected through Principal Coordinate Analysis, neighbor-joining dendrogram and Structure output, with accessions divided into number-of- species-based groups. The study resulted in implications for genetic revision, which, in turn, may clear the misty vision that geneticists might have regarding fescue; and could be exploited in future genetic resources conservation and breeding programs.
Keywords: Festuca; genetic diversity; genetic structure; ISSR; Molecular marker; phylogenetic